2011
DOI: 10.1016/j.optlaseng.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model for light propagation and light intensity distribution inside coated fused silica capillaries

Abstract: Numerical simulations of light propagation through capillaries have been reported to a limited extent in the literature for uses such as flow-cell design. These have been restricted to prediction of light path for very specific cases to date. In this paper, a new numerical model of light propagation through multi-walled cylindrical systems, to represent coated and uncoated capillaries is presented. This model allows for light ray paths and light intensity distribution within the capillary to be predicted. Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The optical output of both devices was measured for different bias currents (20,50 and 75 mA) (Fig. 4B) and as expected the optical power was proportional to the bias current.…”
Section: µ-Led-if-of Device Characterisationsupporting
confidence: 74%
See 1 more Smart Citation
“…The optical output of both devices was measured for different bias currents (20,50 and 75 mA) (Fig. 4B) and as expected the optical power was proportional to the bias current.…”
Section: µ-Led-if-of Device Characterisationsupporting
confidence: 74%
“…A number of LED-IF detection designs for microfluidic chip-based CE [47][48][49][50] systems have been reported as well.…”
Section: ) Australian Centre For Research On Separation Science and mentioning
confidence: 99%
“…The reason for the increased rate of polymer growth is assumed to be from light scattering within the capillary. The propagation of light through fused-silica capillaries has already been well-documented, , and it has been shown that the capillary can transmit a considerable amount of light along its length. During dynamic fabrication, the capillary was exposed to some UV radiation before being drawn into the UV chamber, because of light propagation along the capillary.…”
Section: Resultsmentioning
confidence: 99%